Effectiveness of Digital Learning Media on Students' Achievement in Science Education: A Quasi-Experimental Study in Islamic Junior Secondary School (Jurnal Pendidikan Fisika, 2025)
The rapid expansion of digital technology compels schools to adopt learning media that elevate achievement and cultivate twenty-first-century competencies. In science education, conventional teacher-centered instruction often fails to sustain engagement or deepen conceptual understanding, creating an urgent need for evidence-based innovations. This study examined the effectiveness of digital learning media in improving science achievement at MTs Muhammadiyah Datarang, an Islamic junior secondary school. A quantitative quasi-experimental design was implemented with two intact classes: an experimental group (n = 27) taught using digital media and a control group (n = 26) taught conventionally. Data were collected via pretest–posttest instruments and analyzed using descriptive statistics, normalized gain (N-Gain), and independent-samples t tests. Results showed that the experimental group attained a mean posttest score of 91.41 and an average N-Gain of 0.70 (high), whereas the control group achieved a score of 80.42 and a N-Gain of 0.27 (low); the difference was statistically significant (p < 0.05). These findings indicate that digital media enhance conceptual understanding, engagement, and motivation compared with traditional instruction. The study’s novelty lies in providing rigorous quantitative evidence from a madrasah context that is underrepresented in the technology-enhanced science learning literature. Integrating interactive, visual, feedback-oriented tools can transform science learning in Islamic schools by enabling deeper processing and more equitable progress. This research contributes to physics education by presenting a practical model aligned with multimedia learning theory, providing classroom benchmark values, and informing teacher development and school-level policy. Future studies should extend the intervention longitudinally, involve larger and more diverse samples, and examine affective and social outcomes to evaluate the sustainability and generalizability of the gains.
Keywords: digital learning media; student achievement; science education; quasi-experimental; Islamic school